1990
DOI: 10.1063/1.347181
|View full text |Cite
|
Sign up to set email alerts
|

Growth of native oxide on a silicon surface

Abstract: The control factors controlling the growth of native silicon oxide on silicon (Si) surfaces have been identified. The coexistence of oxygen and water or moisture is required for growth of native oxide both in air and in ultrapure water at room temperature. Layer-by-layer growth of native oxide films occurs on Si surfaces exposed to air. Growth of native oxides on n-Si in ultrapure water is described by a parabolic law, while the native oxide film thickness on n+-Si in ultrapure water saturates at 10 Å. The nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

42
505
0
8

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 822 publications
(555 citation statements)
references
References 23 publications
42
505
0
8
Order By: Relevance
“…1). [75][76][77][78] Hydrogenated silicon surfaces are attractive to work with because of their ease of preparation, 78 their relative stability in air 79,80 and during brief water ring procedures, 31,76 and their lack of appreciable reactivity toward a range of common solvents (including acetonitrile, 81 diethyl ether, 46 chlorobenzene, 82 hexane, 83 toluene 84 and mesitylene 85,86 preparation of covalent organic layers by wet chemical methods. 87 Notable exceptions to the typically straightforward conditions are [2+2] and [4+2] cycloaddition reactions under 'dry' UHV conditions.…”
Section: Surface Preparationmentioning
confidence: 99%
“…1). [75][76][77][78] Hydrogenated silicon surfaces are attractive to work with because of their ease of preparation, 78 their relative stability in air 79,80 and during brief water ring procedures, 31,76 and their lack of appreciable reactivity toward a range of common solvents (including acetonitrile, 81 diethyl ether, 46 chlorobenzene, 82 hexane, 83 toluene 84 and mesitylene 85,86 preparation of covalent organic layers by wet chemical methods. 87 Notable exceptions to the typically straightforward conditions are [2+2] and [4+2] cycloaddition reactions under 'dry' UHV conditions.…”
Section: Surface Preparationmentioning
confidence: 99%
“…The purely mechanical alternative mechanisms ignore the role of stress-induced oxide thickening, which has been observed now by several investigators. 11,12,18,22 Furthermore, this brings into question whether the polysilicon films utilized in earlier studies were representative due to their relatively thick post-release oxide scales ͑typically ϳ20-30 nm 12 rather than the order of a magnitude smaller native oxide layers expected for polysilicon 31 ͒. Pierron et al, 32 however, have recently shown that the relatively thick post-release oxide layers found in these devices, which were all fabricated in the multiuser MEMS process ͑MUMPs͒ foundry, 33,34 arise from a galvanic effect of the n + -type silicon and gold in concentrated HF during release of the freestanding structures at the end of the fabrication process, a finding that was later confirmed.…”
Section: Introductionmentioning
confidence: 97%
“…There is indeed an oxide layer with thickness of 3 nm above the top a-Si layer. Based on previous investigations [13,14], the surface of the a-Si layer Figure 2b. The transmittance decreases with increasing number of layers.…”
Section: Experiments and Resultsmentioning
confidence: 96%
“…There is indeed an oxide layer with thickness of 3 nm above the top a-Si layer. Based on previous investigations [13,14], the surface of the a-Si layer in contact with air would be oxidized to form and an ultra-thin layer an oxide layer with a thickness of only 3 nm on the top. According to our calculation, the oxidation only shifts the center wavelength with only 2 nm and reduces the peak value in transmittance only 0.4%.…”
Section: Experiments and Resultsmentioning
confidence: 99%